Antioxidant Activity Test of Ethanol Extract and Seburo Leaf Fraction (Garcinia forbesii King) in Male Wistar Rats Induced by CCl4 - Salni Salni; Vitri Agustiarini; Gina Nurhasana (Biology, Medicine, & Natural Product Chemistry, 2026)
Seburo (Garcinia forbesii King) leaves have long been used in traditional medicine in Eastern Indonesia. Previous in vitro studies have demonstrated their significant antioxidant potential. This study aimed to characterize the phytochemical composition and evaluate the in vivo antioxidant activity of ethanol extracts and solvent fractions of Seburo leaves using a CCl?-induced hepatotoxicity model in male Wistar rats. Antioxidant efficacy was assessed through measurements of malondialdehyde (MDA) levels, catalase enzyme activity, and both macroscopic and histopathological evaluation of liver tissue. Rats were divided into six groups: negative control (1% Na-CMC), positive control (vitamin C, 10 mg/kg BW), and four treatment groups receiving ethanol extract, n-hexane fraction, ethyl acetate fraction, and ethanol-water fraction (each at 100 mg/kg BW). The n-hexane fraction exhibited the strongest antioxidant activity, with significantly lower MDA levels (0.748 ± 0.061 nmol/mL) and higher catalase activity (27.694 ± 1.135 U/mL), comparable to the positive control. Liver examination revealed reduced tissue damage in all treatment groups compared to the negative control. GC-MS analysis identified key terpenoid compounds in ethanol extract, namely, lupeol, ?-copaene, phytol, and friedelan-3-one, likely contributing to the antioxidant activity. N-hexane fraction has the most significant antioxidant activity among fractions, presumably as it contains the most diverse phytochemical profile. These findings support the therapeutic potential of Seburo leaf as a natural antioxidant agent.